Hungarian Monitoring, 2 November 1989 . [Magyar rádiófigyelő], 1989. november 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Changes in the GDR - Soviet legislature approves 40% increase in pensions - Warsaw Pact member countries' meeting in Sofia - Soviet citizen among protesters at Wenceslaus Square in Prague Domestic Affairs: - Government in session - Bush - Pozsgay meeting - Mátyás Szűrös's tour of the provinces - Warsaw Pact membership - Financial situation of the Interior Ministry - József Antall on membership of the Council of Europe Economy: - Customs allowance from the US - Financing agreement with IMF - Destruction of large companies worse than nationalization: Opposition Chamber of Commerce formed - Finnish government guarantees USD 100 million credit for Hungary Külpolitika: - Az NDK-változások - A szovjet törvényhozás 40 %-os nyugdíjemelést szavazott meg - A VSZ tagországok szófia találkozója - Szovjet állampolgár is volt a Vencel téri tüntetők között Prágában Belpolitika: - Kormányülés - Bush-Pozsgay találkozó - Szűrös Mátyás vidéki körúton - VSZ - Tagság - A BM anyagi helyzete - Antall József az Európa Tanács tagságról Gazdaság: - Vámkedvezmény az USA-tól - Finanszírozási szerződés a Nemzetközi Valuta Alappal - A nagyvállalatok szétverése rosszabb, mint az államosítás: Ellenzéki Gazdasági Kamara alakult - A finn kormány 100-miIlió dollár hitelt biztosít Magyarországnak